Corporate Uses of Credit Derivatives - Wee, Teresa (2006)
Corporate use of derivatives is not something that is new today. Firms often make use of them to do risk management when they have exposures to interest rate and exchange rate risks in the course of running their business. More recently, the use of credit derivatives to manage credit risks has also become one option that firms use. However, the usage of this option has been less frequently utilised largely due to the lack of understanding of credit derivatives by corporate firms. Firms have chosen more traditional but not always convenient methods, such as insurance and letters of credit to manage their credit exposure.